Disruptive Change in Nursing Education: From the Situation of the Spread of the Coronavirus Disease 2019 to Online Learning - Buachu, Thinnakorn; Sirirat, Nutkawee; Noimorkunladech, Napattamon; Muangkaew, Prapaporn (Journal of The Royal Thai Army Nurses, 2021)
Learning management problems in an epidemic situation of COVID-19 causes a disruptive change of the nursing education system, changing classroom teaching through online self-learning from home to keep the social distancing. Those affect the online education system through a new learning platform and the information technology for education more active. Skills in using computers, information technology and communication is very important for learners and teachers. Therefore, the development of educational personnel must be appropriate with the new learning culture, adaptation of learners are challenges. In this regard, the design of the educational management system must be consistent with the bachelor’s degree of nursing and educational management standards in the 21st century and provide learning appropriate for changing situations, linking knowledge to the practical implementation of health care which more severe and complex.